Anisotropic conductive film, connection structure and method for manufacturing the same
A multilayered anisotropic conductive film with specific resin components achieves robust adhesion, reliable connectivity, and stable slitting, addressing issues of adhesive strength and visibility in high humidity environments.
Patent Information
- Application Number
- JP2023109297
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-17
AI Technical Summary
Existing anisotropic conductive films face issues with insufficient initial adhesive strength, reduced connection reliability in high temperature and humidity environments, poor visibility of conductive particle indentations, and difficulty in slitting into narrow widths due to resin adherence and blocking during processing.
A multilayered anisotropic conductive film structure comprising a radically polymerizable conductive particle-containing resin layer and a radically and anionically polymerizable insulating resin layer, using specific components like phenoxy resins, acrylic compounds, epoxy compounds, and organic peroxides to achieve hybrid curing, ensuring good adhesion, visibility, and slitting stability.
The film provides excellent initial adhesive strength, maintains connection reliability in humid conditions, ensures clear visibility of conductive particle indentations, and allows stable slitting into narrow widths, enhancing connectivity in electronic components.
Smart Images

Figure 2025007716000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anisotropic conductive film, a connection structure, and a method for manufacturing the same. [Background technology]
[0002] Resin films in which conductive particles are dispersed or regularly arranged in an insulating resin layer are widely used as anisotropic conductive films. As such anisotropic conductive films, from the viewpoint of low-temperature, short-time curing (low-temperature fast curing), a film has been proposed in which conductive particles are mixed into a radical polymerizable resin composition containing a radical polymerizable compound such as (meth)acrylates and a radical polymerization initiator (organic peroxide) and the film is molded (Patent Document 1), and from the viewpoint of good adhesive strength, heat resistance, water resistance, and flexibility, a film has been proposed in which conductive particles are mixed into an anionic polymerizable resin composition containing an anionic polymerizable epoxy compound, a glycidyl ether group-containing acrylic rubber, and an anionic polymerization curing agent and the film is molded (Patent Document 2).
[0003] In recent years, from the viewpoint of simultaneously achieving the advantages of producing an anisotropic conductive film from such a radical polymerizable resin composition (low-temperature rapid curing property) and the advantages of producing an anisotropic conductive film from an anionic polymerizable resin composition (good adhesive strength, heat resistance, water resistance, and flexibility), a hybrid curable resin composition containing a radical polymerizable compound, an anionic polymerizable compound, a radical polymerization initiator, and an anionic polymerization curing agent has been proposed in which conductive particles are mixed with the composition and the composition is molded into a film (Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO1998044067 Brochure [Patent Document 2] WO1998003047 Brochure [Patent Document 3] JP 2007-224228 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the initial adhesive strength of the semiconductor device obtained by anisotropically conductively connecting an IC chip to a circuit board using the anisotropic conductive film disclosed in Patent Document 3 may not be sufficient, and if the semiconductor device thus obtained is mistakenly placed in a high-temperature and high-humidity environment, there is a problem that the connection reliability is reduced, or even if the connection reliability is not reduced, the visibility of the conductive particle impressions at the connection part of the connection structure is reduced, and floating occurs at the connection part. In addition, in order to miniaturize the connection structure and to mount it at a high density, it is required to slit the anisotropic conductive film to a narrow width, but the anisotropic conductive film disclosed in Patent Document 3 may cause adhesion of resin to the slit blade or blocking in the wound body of the anisotropic conductive film after slitting, making it difficult to slit the film to a narrow width stably.
[0006] The object of the present invention is to solve the problems of the related art, and to provide an anisotropic conductive film obtained by mixing conductive particles into a hybrid curing resin composition containing a radical polymerizable compound, an anionic polymerizable compound, a radical polymerization initiator, and an anionic polymerization curing agent, and molding the mixture into a film to obtain an anisotropic conductive connection between a first electronic component and a second electronic component, which exhibits low-temperature rapid curing properties and achieves good initial adhesive strength in the connection structure, and further, even if the connection structure is mistakenly placed in a high-temperature and high-humidity environment, the connection reliability is not reduced, good visibility of the conductive particle impressions in the connection portion of the connection structure is ensured, and floating is not generated in the connection portion, while the anisotropic conductive film itself can be stably slit into narrow widths. [Means for solving the problem]
[0007] The inventors have discovered that by multi-layering an anisotropic conductive film with a radically polymerizable conductive particle-containing resin layer composed of specific components and a radically polymerizable and anionically polymerizable insulating resin layer, it is possible to achieve not only low-temperature rapid curing properties but also good initial adhesive strength for the connection structure, and further, even if the connection structure is mistakenly placed in a high-temperature and high-humidity environment, the connection reliability is not reduced, good visibility of the conductive particle impressions at the connection portion of the connection structure is ensured, and floating is prevented from occurring at the connection portion, and further the anisotropic conductive film can be stably slit to narrow widths, thereby completing the present invention.
[0008] That is, the present invention provides an anisotropic conductive film having an insulating resin layer exhibiting radical polymerizability and an anionic polymerizability and a conductive particle-containing resin layer exhibiting radical polymerizability laminated thereon, wherein the insulating resin layer contains the following components A, B, C, D, and E, and the conductive particle-containing resin layer contains the following components a to d.
[0009] <Insulating resin layer> (Component A) a film-forming component containing a first phenoxy resin having a weight-average molecular weight of 50,000 or more and 80,000 or less, and a second phenoxy resin having a weight-average molecular weight of 30,000 or more and less than 50,000; (Component B) a radically polymerizable component containing a first acrylic compound; (Component C) an anionically polymerizable component containing an epoxy compound; (Component D) A radical polymerization initiator containing an organic peroxide having a 1-minute half-life temperature of 125°C or less; and (Component E) An anionic polymerization hardener containing an organic acid hydrazide compound with a melting point of 160°C or less.
[0010] <Resin layer containing conductive particles> (Component a) a third film-forming component containing a phenoxy resin; (component b) a radically polymerizable component containing a second acrylic compound; (component c) Conductive particles; and (ingredient d) A radical polymerization initiator containing an organic peroxide with a one-minute half-life temperature of 125°C or less.
[0011] The present invention also provides a connection structure in which a first electronic component and a second electronic component are anisotropically conductively connected via the anisotropic conductive film of the present invention.The present invention also provides a method for producing a connection structure in which the anisotropic conductive film of the present invention is sandwiched between the first electronic component and the second electronic component and pressure-bonded to achieve anisotropic conductive connection. Effect of the Invention
[0012] The anisotropic conductive film of the present invention is multi-layered with a radically polymerizable conductive particle-containing resin layer composed of specific components and a radically polymerizable and anionically polymerizable insulating resin layer. In the insulating resin layer, hybrid curing by anionic polymerization and radical polymerization can improve the crosslink density and improve the adhesiveness of the insulating resin layer. Therefore, the anisotropic conductive film of the present invention exhibits low-temperature rapid curing properties, and realizes good initial adhesive strength in a connection structure manufactured using the anisotropic conductive film of the present invention. Moreover, even if the connection structure is mistakenly placed in a high-temperature and high-humidity environment, the connection reliability is not reduced, and good visibility of the conductive particle impressions at the connection part of the connection structure is ensured, and floating is prevented from occurring at the connection part. Furthermore, such an anisotropic conductive film itself can be stably slit into a narrow width. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view of an anisotropic conductive film of the present invention. [Diagram 2] FIG. 2 is a diagram of a connection structure used to explain inspection of the floating state of a connection portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.
[0015] <<Anisotropic conductive film>> As shown in FIG. 1, the anisotropic conductive film 10 of the present invention has an insulating resin layer 1 exhibiting radical polymerization and an anion polymerization, and a conductive particle-containing resin layer 2 exhibiting radical polymerization laminated thereon. Usually, a release base film 4 necessary for applying an insulating resin layer forming composition during the manufacture of an anisotropic conductive film may be arranged on the insulating resin layer 1 side. Similarly, a release base film may be arranged on the conductive particle-containing resin layer 2 side. Thus, in the present invention, the anisotropic conductive film 10 has a laminated structure in which a radically polymerizable and anionically polymerizable insulating resin layer 1 that does not contain conductive particles is laminated with a radically polymerizable conductive particle-containing resin layer 2 that contains conductive particles 3. Moreover, each layer contains the same type of phenoxy resin as a film-forming component. When a first electronic component and a second electronic component are anisotropically conductively connected using the anisotropic conductive film of the present invention configured in this way, a sufficient amount of adhesive resin can be present between them to realize good initial adhesive strength. In the conductive particle-containing resin layer 2, the conductive particles 3 may be randomly dispersed and held in the conductive particle-containing resin layer 2, or may be regularly arranged.
[0016] <Constituents of insulating resin layer 1> The insulating resin layer 1 contains the following components A, B, C, D, and E. Each component will be explained below.
[0017] (Component A) Component A is a film-forming component containing two types of phenoxy resins with different weight-average molecular weights. In the present invention, two types of phenoxy resins with different weight-average molecular weights, in other words, a first phenoxy resin with a relatively high molecular weight and a second phenoxy resin with a relatively low molecular weight, are used in combination as the film-forming component. The reason for this combination is that when an anisotropic conductive film having an insulating resin layer 1 using only a first phenoxy resin with a relatively high molecular weight as component A is slit, if a release base film 4 with a high elastic modulus and high impact resistance is present, the anisotropic conductive film can be prevented from being displaced from the release base film 4 due to the impact of the slit blade. However, since the tackiness of the insulating resin layer 1 is somewhat low, the adhesion to the release base film 4 is reduced, and there is a concern that floating will occur. On the other hand, when an anisotropic conductive film having an insulating resin layer 1 using only a second phenoxy resin with a relatively low molecular weight as component A is slit, the resin is likely to adhere to the slit blade during slitting, and there is a concern that blocking will occur. Therefore, by using two types of phenoxy resins with different weight-average molecular weights in combination, the flexibility of the insulating resin layer 1 and its adhesion to the release base film 4 can be improved, and the insulating resin layer 1 can be prevented from floating away from the release base film 4. At the same time, when the anisotropic conductive film 10 is slit into a narrow width (e.g., 0.5 mm or less), adhesion of the resin to the slitting blade and the occurrence of blocking can be prevented.
[0018] The weight average molecular weight of the first phenoxy resin having a relatively high molecular weight as described above is specifically 50,000 or more, preferably 55,000 or more, and 80,000 or less, preferably 70,000 or less. The weight average molecular weight of the second phenoxy resin having a relatively low molecular weight is specifically 30,000 or more, preferably 35,000 or more, and less than 50,000, preferably 45,000 or less. The weight average molecular weight can be measured by a normal gel permeation chromatography method.
[0019] If the content of component A (film-forming component) in the insulating resin layer 1 is too small, the anisotropic conductive film will be prone to bending, and if it is too much, the fluidity of the resin during anisotropic conductive connection will decrease, making it difficult to obtain good conductivity, and the flexibility will also decrease, tending to lower the adhesive strength. Therefore, the content is preferably 20.0 mass % or more, more preferably 25.0 mass % or more, and preferably 50.0 mass % or less, more preferably 35.0 mass % or less.
[0020] If the relative content of the second phenoxy resin to the first phenoxy resin in component A is too low, the flexibility and adhesive strength tend to be low, and if it is too high, the elastic modulus during formation of the anisotropic conductive film and the slitting properties tend to be low. Therefore, the content of the second phenoxy resin to 100 parts by mass of the first phenoxy resin is preferably 40 parts by mass or more, and preferably 100 parts by mass or less.
[0021] The above-mentioned first phenoxy resin and second phenoxy resin can be selected from known phenoxy resins, but are generally epoxy group-free polyhydroxy polyethers (thermoplastic resins) synthesized from bisphenols and epichlorohydrin, and a preferred bisphenol component is bisphenol A from the viewpoint of availability. Therefore, a bisphenol A-type phenoxy resin can be preferably used as the first phenoxy resin and the second phenoxy resin of component A.
[0022] In addition, component A may contain general film-forming components other than the first phenoxy resin and the second phenoxy resin, such as epoxy resins, polyester resins, urethane resins, butadiene resins, polyamide resins, polyimide resins, polyolefin resins, polyvinyl butyral resins, and ethylene-vinyl acetate copolymer resins, as long as the effects of the present invention are not impaired.
[0023] (Component B) Component B is a radical polymerizable component containing a first acrylic compound. Examples of the first acrylic compound include known monofunctional (meth)acrylates such as alkyl (meth)acrylates, polyfunctional (meth)acrylates such as polypropylene glycol di(meth)acrylates, and urethane (meth)acrylates. Among them, urethane (meth)acrylates, which are reaction products of hydroxyalkyl (meth)acrylates and diisocyanates, are preferred from the viewpoint of improving adhesion to polyimide of flexible printed circuit boards (FPCs) in order to improve the cohesive force of the cured product and improve the electrical connection reliability. These first acrylic compounds may be monomers, oligomers, or polymers. In addition, the polyfunctional (meth)acrylates can also function as crosslinking agents, and isocyanuric acid EO-modified di- or tri(meth)acrylates can be preferred as crosslinking agents. In addition, (meth)acrylate is a term meaning both acrylate and methacrylate.
[0024] The content of component B (radical polymerizable component) in the insulating resin layer 1 is preferably 20.0 mass% or more, more preferably 30.0 mass% or more, and preferably 50.0 mass% or less, more preferably 40.0 mass% or less, because if the content is too low, the cohesive force of the insulating resin is weakened and the desired adhesive strength cannot be achieved in the anisotropic conductive film, and if the content is too high, the liquid component increases relatively, the insulating resin layer becomes soft, and there is a concern that it may adhere to the slit blade. Note that component B can contain a radical polymerizable component other than the first acrylic compound, such as an alkene compound, as long as it does not impair the effects of the present invention.
[0025] (Component C) Component C is an anionically polymerizable component containing an epoxy compound. The epoxy compound includes compounds having two or more epoxy groups in one molecule and capable of three-dimensional curing in the presence of a curing agent or catalyst. Such epoxy compounds include epoxy group-containing reaction products of bisphenols and epichlorohydrin, preferably bisphenol A-type liquid epoxy resins. This reaction product can be in the form of an oligomer or prepolymer.
[0026] If the content of component C (anionic polymerizable component) in the insulating resin layer 1 is too small, the cohesive strength will decrease and lifting will be more likely to occur at the interface between the anisotropic conductive film and the FPC, while if the content is too large, there is a concern that the toughness will decrease and the adhesive strength will also decrease. Therefore, the content is preferably 1.0 mass % or more, more preferably 5.0 mass % or more, preferably less than 20.0 mass %, and more preferably 10.0 mass % or less.
[0027] (Component D) Component D is a radical polymerization initiator containing an organic peroxide having a one-minute half-life temperature of 125° C. or less, preferably 100° C. or more and 120° C. or less. By using such an organic peroxide, the radical polymerizable component of Component B can be rapidly cured at a low temperature of 150° C. or less.
[0028] Specific examples of organic peroxides (one-minute half-life temperatures) of component D are shown below. Diisobutyl peroxide (85.1℃) Cumyl peroxy neodecanoate (94.0℃) Di-n-propyl peroxydicarbonate (94.0℃) Diisopropyl peroxydicarbonate (88.3℃) Di-sec-butyl peroxydicarbonate (92.4℃) 1,1,3,3-Tetramethylbutylperoxyneodecanoate (92.4℃) Di(4-t-butylcyclohexyl) peroxydicarbonate (92.1℃) Di(2-ethylhexyl) peroxydicarbonate (90.6℃) t-Hexyl peroxy neodecanoate (100.9℃) t-Butyl peroxyneodecanoate (103.5℃) t-Hexylperoxypivalate (109.1℃) t-Butyl peroxypivalate (110.3℃) Di(3,5,5-trimethylhexanoyl)peroxide (112.6℃) Dilauryl peroxide (116.4℃) 1,1,3,3-Tetramethylbutylperoxy-2-ethylhexanoate (124.3℃) 2,5-Dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (118.8℃)
[0029] Among the above organic peroxides, dilauroyl peroxide (116.4°C) can be preferably used because it can obtain properties such as electrical continuity, indentation, and adhesiveness even when pressure-bonded at a low temperature condition of 150°C. The content of component D in the insulating resin layer 1 can be appropriately determined in consideration of the content of component B (radical polymerizable component) and the pressure-bonding properties and tackiness of the insulating resin layer 1, but it can also be determined in consideration of the content of component E (anionic polymerization curing agent) in terms of crosslink density. This point will be described later.
[0030] (Component E) Component E is an anionic polymerization curing agent containing an organic acid hydrazide compound having a melting point of 160°C or less, preferably 80°C to 160°C, in order to anionically polymerize the anionic polymerizable component of component C. The reason for using an anionic polymerization curing agent in component E is that if only a radical polymerization initiator is used as the polymerization initiator, the cohesive force of the film is insufficient, and there is a concern that floating may occur, and in order to eliminate such concerns, a hybrid curing of radical polymerization and anionic polymerization is realized. In addition, the reason for using an organic acid hydrazide compound as an anionic polymerization curing agent is that it can be handled in the form of microcrystals or fine powder, and therefore a one-liquid curing type resin compound can be easily obtained by blending it with a resin. The reason for using one having a melting point of 160°C or less is that there is a concern that the low-temperature rapid curing property will be impaired if an organic hydrazide compound having a melting point of more than 160°C is used. Such an organic acid hydrazide compound can be selected from known aliphatic dicarboxylic acid hydrazides and aromatic carboxylic acid hydrazides.
[0031] Specific examples of the organic acid hydrazide compounds (melting points) of Component E are shown below. Salicylic acid hydrazide (147-151℃) 2-Thiophenecarboxylic acid hydrazide (136-139℃) 3-(Phenylamino)propionic acid hydrazide (93-95℃) N,N-Di(carboxyethyl)aniline hydrazide (141-145℃) Eicosanedicarboxylic acid dihydrazide (155-156℃) 7-Ethyl octadecanedicarboxylic acid dihydrazide (50-90℃)
[0032] Among the above-mentioned organic acid hydrazide compounds, salicylic acid hydrazide (147 to 151° C.) can be preferably used from the viewpoint of pot life, since the heat generation amount of the acrylic compound was observed from a low temperature in a differential scanning calorimeter (DSC).
[0033] If the content of component E (anionic polymerization curing agent) in the insulating resin layer 1 is too small relative to the epoxy content, lifting is likely to occur after a pressure cooker test (PCT), while if it is too large, the cohesive strength tends to increase and the storage life of the product tends to be shortened. Therefore, the content is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and is preferably less than 10.0 mass %, more preferably 1.0 mass % or less.
[0034] The thickness of the insulating resin layer 1 containing the above components A to E is preferably 10 μm or more, more preferably 15 μm or more, and is preferably 25 μm or less, more preferably 20 μm or less, since if it is too thin, it becomes difficult to obtain sufficient adhesive strength, and if it is too thick, stable slits tend not to be formed.
[0035] The insulating resin layer 1 may contain various additives used in conventional anisotropic conductive films, such as softeners such as butadiene rubber, fillers (viscosity modifiers) such as silica filler, coloring pigments such as carbon black, adhesion improvers such as silane coupling agents and phosphate compounds, internal release agents such as calcium stearate, etc., within the scope of the invention. A preferred example of the phosphate compound is a reaction product of a 6-hexanolide addition polymer of 2-hydroxyethyl methacrylate with phosphoric anhydride.
[0036] In addition, the content of component E (anionic polymerization curing agent) in the insulating resin layer 1 can be evaluated in terms of its content ratio (by mass) relative to component C (anionic polymerizable component) from the viewpoint of obtaining the amount necessary for the reaction of the epoxy compound that contributes to improving the heat resistance and weather resistance of the insulating resin layer 1 and stable characteristics, as described below, or it can also be evaluated in terms of its content ratio (by mass) relative to component D (radical polymerization initiator) from the viewpoint of maintaining good compression characteristics even if the density of the crosslinked structure changes depending on the reaction ratio of the epoxy compound and the acrylic compound.
[0037] Specifically, the content ratio (by mass) of component E (anionic polymerization curing agent) to component C (anionic polymerizable component) in the insulating resin layer 1 is (= [component E] / [component C])×10 2 If the epoxy resin composition is too low, the reactivity of the epoxy resin will be low and the density of the crosslinked structure will be low, which may cause lifting in a pressure cooker test (PCT). If the epoxy resin composition is too high, there is a risk that lifting will occur in a PCT due to an excess of anionic polymerization hardener. Therefore, the epoxy resin composition is preferably 1 or more, more preferably 2 or more, and is preferably 30 or less, more preferably 20 or less.
[0038] Furthermore, if the content ratio (by mass) of component E (anionic polymerization curing agent) to component D (radical polymerization initiator) in the insulating resin layer 1 is too low, there is a risk that interfacial peeling from the substrate after compression bonding will be more likely to occur, making it difficult to obtain adhesive strength, whereas if the content ratio is too high, there is a tendency that the reactivity of acrylic will be low at 150°C, making it difficult to obtain compression bonding properties. Therefore, the content ratio of component D is preferably 0.1 or more, more preferably 0.2 or more, and preferably 60.0 or less, more preferably 5.0 or less.
[0039] <Constituents of the conductive particle-containing resin layer 2> The conductive particle-containing resin layer 2 constituting the anisotropic conductive film 10 of the present invention contains the following components a to d. Each component will be explained below.
[0040] (Component a) Component a is a film-forming component containing a third phenoxy resin. The reason for using the third phenoxy resin is to improve the adhesion between the insulating resin layer 1 and the conductive particle-containing resin layer 2. There is no particular restriction on the weight average molecular weight or polydispersity of the third phenoxy resin, but it is preferable to use the same one as the first phenoxy resin in order to increase the affinity with the first phenoxy resin, which is relatively abundant in the insulating resin layer 1. Therefore, as the third phenoxy resin of component a, a bisphenol A type phenoxy resin can be preferably used.
[0041] The content of component a (film-forming component) in the conductive particle-containing resin layer 2 is preferably 15.0% by mass or more, more preferably 20.0% by mass or more, preferably 50.0% by mass or less, and more preferably 35.0% by mass or less, because too little makes the film easily bendable, and too much reduces the fluidity of the resin during anisotropic conductive connection, making it difficult to obtain good conductivity, and also reduces flexibility, tending to reduce adhesive strength. Also, component a preferably contains at least 15.0% by mass or more of the third phenoxy resin, but may contain other known film-forming components, such as thermoplastic resins such as polyamides and polyolefins, and thermoplastic elastomers, as long as the effects of the present invention are not impaired.
[0042] (component b) Component b is a radical polymerizable component containing a second acrylic compound. The content of the second acrylic compound in component b is preferably at least 20.0% by mass. As the second acrylic compound, the same one as the first acrylic compound can be used. Among them, urethane (meth)acrylate, which is a reaction product of hydroxyalkyl (meth)acrylates and diisocyanates, can be preferably mentioned from the viewpoint of improving the cohesive force of the cured product to improve the conduction reliability and further improving the adhesion of the FPC substrate to the polyimide. These second acrylic compounds may be monomers, oligomers or polymers. In addition, the multifunctional (meth)acrylate can also function as a crosslinking agent, and isocyanuric acid EO-modified di- or tri(meth)acrylate can be preferably mentioned as a crosslinking agent.
[0043] If the content of component b (radical polymerizable component) in the conductive particle-containing resin layer 2 is too small, the tackiness of the anisotropic conductive film will decrease, adhesion to the glass substrate will decrease, and the elastic modulus of the anisotropic conductive film will decrease even after bonding, tending to reduce connection reliability. If the content is too large, when the anisotropic conductive film is slit and wound around a reel to form a wound body, the resin component is likely to protrude, and there is a concern that the slit anisotropic conductive film cannot be properly pulled out from the wound body (blocking state). Therefore, the content is preferably 20.0 mass % or more, more preferably 30.0 mass % or more, and preferably 50.0 mass % or less, more preferably 40.0 mass % or less.
[0044] (component c) Component c is conductive particles 3 for imparting anisotropic conductivity to the anisotropic conductive film 10. The conductive particles 3 may be the same as known conductive particles used in general anisotropic conductive films. For example, metal particles, alloy particles, metal-coated resin particles, etc. may be appropriately selected and used.
[0045] The average particle diameter of component c (conductive particles 3) is preferably 1.5 μm or more, more preferably 2.0 μm or more, and is preferably equal to or less than the thickness of the conductive particle-containing resin layer, more preferably 5.0 μm or less, since if it is too small, the indentation strength tends to be small, and if it is too large, the insulation reliability between wirings tends to deteriorate. This average particle diameter can be measured by a commercially available particle size distribution measuring device using a laser diffraction / scattering method.
[0046] If the content of the conductive particles 3 of component c in the conductive particle-containing resin layer 2 is too small, the connection reliability of the anisotropic conductive film will be insufficient, and if it is too high, there is a concern that a short circuit will occur, so the content is preferably 5.0 mass % or more, more preferably 7.5 mass % or more, and preferably 45.0 mass % or less, more preferably 35.0 mass % or less.
[0047] The conductive particles 3 of component c may be randomly dispersed and held in the conductive particle-containing resin layer 2, but may also be arranged regularly, for example in a lattice pattern, by a known method. The conductive particles may be held so as to be exposed on the surface of the conductive particle-containing resin layer 2, or may be embedded therein. They may be held so as not to overlap in the film thickness direction when viewed in plan. If the number density of the conductive particles in the film plan view is too low, it is difficult for the particles to be captured on the terminals, and it may not be possible to accommodate narrower picture frames of image display devices or finer pitches of electrodes on circuit boards. If the number density is too high, the insulation reliability between wirings tends to decrease, so that the number density is preferably 3,500 particles / mm. 2 More preferably, 5,000 pieces / mm 2 or more, and preferably 25,000 pieces / mm 2 Less than or equal to 20,000 pieces / mm 2 The following is the result.
[0048] (ingredient d) Like component D of the insulating resin layer 1, component d is a radical polymerization initiator containing an organic peroxide having a one-minute half-life temperature of 125°C or less, preferably 100°C to 120°C. By using such an organic peroxide, the radical polymerizable component of component b can be cured quickly at low temperature. Among them, dilauroyl peroxide (116.4°C) can be preferably used because it can obtain pressure-bonding properties at 150°C.
[0049] If the content of component d (radical polymerization initiator) in the conductive particle-containing resin layer 2 is too small relative to component b (radical polymerizable component), it becomes difficult to obtain pressure-bonding properties from 150°C, and if it is too much, tackiness tends to be reduced. Therefore, the content is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and preferably 30 parts by mass or less, more preferably 20 parts by mass or less, relative to 100 parts by mass of component b (radical polymerizable component).
[0050] The thickness of the conductive particle-containing resin layer 2 containing the above components a to d is preferably equal to or greater than the conductive particle diameter, more preferably equal to or greater than 3 μm, and more preferably equal to or less than 10 μm, more preferably equal to or less than 7 μm, since if it is too thin, it becomes difficult to obtain sufficient adhesive strength, and if it is too thick, the conductivity reliability tends to decrease.
[0051] The conductive particle-containing resin layer 2 may contain various additives used in conventional anisotropic conductive films, such as softeners such as butadiene rubber, fillers (viscosity modifiers) such as silica filler, coloring pigments such as carbon black, adhesion improvers such as silane coupling agents and phosphate compounds, internal release agents such as calcium stearate, etc., within the scope of not impairing the effects of the present invention. A preferred example of the phosphate compound is a reaction product of a 6-hexanolide addition polymer of 2-hydroxyethyl methacrylate with phosphoric anhydride.
[0052] <Release base film 4> In the anisotropic conductive film 10 of the present invention, a release base film 4 is provided on the insulating resin layer 1 side as necessary, and can function as a film to which the insulating resin layer forming composition is applied when the insulating resin layer 1 side is formed. In addition, a release base film may also be provided on the conductive particle-containing resin layer 2 side as a cover film. As such a release base film 4, a known release base film applied to a normal anisotropic conductive film can be adopted. For example, a polyethylene terephthalate film treated with silicone release treatment can be used as the release base film.
[0053] <<Manufacturing of anisotropic conductive film>> The anisotropic conductive film of the present invention is prepared by applying an insulating resin layer-forming composition obtained by uniformly mixing components A to E together with a general-purpose solvent as necessary to one side of a release base film such as a release-treated polyethylene terephthalate film in a conventional manner, for example with a bar coater, and drying the composition to form an insulating resin layer; similarly, a conductive particle-containing resin layer-forming composition obtained by uniformly mixing components a to d together with a general-purpose solvent as necessary to one side of another release base film in a conventional manner, and drying the composition to form a conductive particle-containing resin layer; and then laminating the insulating resin layer and the conductive particle-containing resin layer facing each other to produce an anisotropic conductive film having a laminated structure of release base film / insulating resin layer / conductive particle-containing resin layer / release base film (cover film).
[0054] The anisotropic conductive film of the present invention thus manufactured can be slit into a narrow width, wound on a reel, and distributed as a wound body, and in such a wound body, not only the resin overflow phenomenon but also blocking is greatly suppressed. From the viewpoint of practicality, the film length in such a wound body is preferably 5 m or more, more preferably 50 m or more, preferably 5000 m or less, more preferably 1000 m or less. In addition, the release force between the insulating resin layer 1 and the release base film 4 in the anisotropic conductive film of the present invention is preferably 200 to 400 mN / 5 cm, more preferably 250 to 350 mN / 5 cm, according to a T-type release test according to JIS K 6854. If it is below this range, the anisotropic conductive film is likely to float from the release base film during slitting, and blocking tends to occur, and if it is above this range, the anisotropic conductive film tends to be difficult to attach to glass when used.
[0055] <<Applications of Anisotropic Conductive Film>> The anisotropic conductive film of the present invention can be preferably used when anisotropically conductively connecting a first electronic component such as an FPC, an IC chip, or an IC module to a second electronic component such as an FPC, a rigid substrate, a ceramic substrate, a glass substrate, or a plastic substrate. The connection structure thus obtained, that is, a connection structure in which a first electronic component and a second electronic component are anisotropically conductively connected via the anisotropic conductive film of the present invention, is also part of the present invention. In addition, a manufacturing method of a connection structure in which anisotropic conductive connection is performed by sandwiching the anisotropic conductive film of the present invention between the first electronic component and the second electronic component and pressing them is also part of the present invention. EXAMPLES
[0056] The present invention will be specifically described below with reference to examples and comparative examples.
[0057] <Preparation of composition for forming conductive particle-containing resin layer> PMA (propylene glycol monomethyl ether acetate) was added to the components in Table 1 so that the solid content was 45 mass %, and the mixture was mixed uniformly to prepare compositions A1 and A2 for forming conductive particle-containing resin layers.
[0058] <Preparation of composition for forming insulating resin layer> Compositions N1 to N15 for forming an insulating resin layer were prepared by adding PMA to the blending components shown in Tables 2A and 2B so that the solid content was 42 mass % and mixing them uniformly.
[0059] [Table 1]
[0060] [Table 2A]
[0061] [Table 2B]
[0062] <<Examples 1 to 10, Comparative Examples 1 to 7>> (Formation of conductive particle-containing resin layer) A conductive particle-containing resin layer-forming composition was prepared by adding propylene glycol monomethyl ether acetate (PMA) to the formulation (A1 or A2) in Table 1 so that the solid content was 45 mass % and mixing uniformly. The composition was applied to a 25 μm-thick polyethylene terephthalate release base film having a silicone release-treated surface using a bar coater so that the dry thickness was 5 ± 0.5 μm, and the composition was dried in an oven at 55 ° C for 3 minutes to form a conductive particle-containing resin layer on the release base film.
[0063] (Formation of insulating resin layer) Separately from the conductive particle-containing resin layer, PMA was added to the formulations (N1 to N15) in Tables 2A and 2B so that the solid content was 42 mass%, and the mixture was mixed uniformly to prepare a composition for forming an insulating resin layer. The composition was applied to a 50 μm-thick polyethylene terephthalate release base film having a silicone release-treated surface with a bar coater so that the dry thickness was 15±0.5 μm, and the composition was dried in an oven at 70° C. for 4 minutes to form an insulating resin layer on the release base film.
[0064] (Formation of anisotropic conductive film) The obtained insulating resin layer and the conductive particle-containing resin layer were placed opposite each other and laminated under conditions of 45°C and 0.5 MPa to obtain an anisotropic conductive film having a laminated structure of release base film / insulating resin layer / conductive particle-containing resin layer / release base film (cover film). However, Comparative Example 6 was an anisotropic conductive film having a single layer of conductive particle-containing resin layer without an insulating resin layer, and Comparative Example 7 was an anisotropic conductive film having a single layer of insulating resin layer without a conductive particle-containing resin layer. A general cover film was laminated at 45°C on the exposed conductive particle-containing resin layer.
[0065] <<Evaluation>> The anisotropic conductive films of the examples and comparative examples were tested or inspected and evaluated for "slit processability," "initial adhesive strength," "connection reliability," "visibility of indentation," and "state of floating of connection portion" as described below. The obtained results are shown in Table 3.
[0066] <Slitting processability> After peeling off the cover film from 100 m of each of the anisotropic conductive films of Examples 1 to 10 and Comparative Examples 1 to 7, the film was slit to a width of 0.5 mm using a general slitting device to create anisotropic conductive film tape, which was then evaluated according to the following evaluation criteria.
[0067] (Slitting processability evaluation criteria) Rank Evaluation criteria A: When not only does the resin not adhere to the slit blade, but the insulating resin layer is able to be slit without floating away from the release base film. B: A small amount of resin adhered to the slit blade, but there was no practical problem with the anisotropic conductive film after slitting. C: When resin adheres to the slit blade or the insulating resin layer floats off the release base film.
[0068] <Initial adhesive strength> Each anisotropic conductive film produced in the examples and comparative examples was slit to a width of 0.5 mm, and the cover film was peeled off to obtain a tape-shaped anisotropic conductive film. Next, the tape-shaped anisotropic conductive film was temporarily attached to the edge of an ITO glass substrate (0.7 mm thick) on which an indium tin oxide transparent electrode was formed, from the conductive particle-containing resin layer, and placed on a hot plate at 45 ° C., and uniformly pressed from the release base film side on the insulating resin layer side. Thereafter, the release base film was released, and the metal wiring part of the evaluation FPC (thickness 50 μm) was attached so that the exposed insulating resin layer side was completely covered, and the FPC and the glass substrate were further thermocompressed (150 ° C., 4 MPa, 5 seconds) to bond the opposing electrodes of the FPC and the glass substrate with the cured product of the anisotropic conductive film, thereby obtaining a connection structure with anisotropic conductive connection. The FPC specifications were polyimide film thickness 66 μm, copper circuit thickness 20 μm, and copper circuit line width 60 μm (pitch 120 μm, L / S=1 / 1).
[0069] The resulting connection structure including the FPC for evaluation was cut to a width of 1 cm, and a tensile tester (RTC1201, A&D Co., Ltd.) was used to measure the adhesive strength when the FPC for evaluation was pulled up at an angle of 90° at a speed of 50 mm / sec, and the adhesive strength was evaluated according to the following criteria. For practical purposes, a rating of B is acceptable, and a rating of A is more preferable.
[0070] (Initial adhesive strength evaluation criteria) Rank Evaluation criteria A: The adhesive strength is 7N / cm or more. B: The adhesive strength is 5N / cm or more and less than 7N / cm. C: The adhesive strength is less than 5N / cm.
[0071] <Connection reliability> As in the case of the initial adhesive strength test, a connection structure was obtained by anisotropically conductively connecting a glass substrate and an FPC using each of the anisotropic conductive films produced in the examples and comparative examples. However, instead of an FPC with a polyimide film thickness of 66 μm, a copper circuit thickness of 20 μm, and a copper circuit line width of 60 μm (pitch 120 μm, L / S=1 / 1), an FPC with a polyimide film thickness of 44 μm, a copper circuit thickness of 20 μm, and a copper circuit line width of 60 μm (pitch 120 μm, L / S=1 / 1) was used.
[0072] The conductive resistance between the anisotropically conductively connected electrodes of the obtained connection structure was measured by a four-terminal method immediately after the production of the connection structure (initial stage) and after a pressure cooker test (PCT) in which the connection structure was held in a thermo-hygrostat (110°C, 85% RH) for 24 hours, and was evaluated according to the following criteria. In practical terms, a rating of B is sufficient, and a rating of A is more preferable.
[0073] (Connection reliability evaluation criteria) Rank Evaluation criteria A: The conductive resistance is less than 5 Ω. B: The conductive resistance is between 5 Ω and 10 Ω. C: Conduction resistance is 10 Ω or more.
[0074] <Indentation visibility inspection> As in the case of the connection reliability test, a connection structure was obtained by anisotropically conductively connecting a glass substrate and an FPC using each anisotropic conductive film produced in the examples and comparative examples. However, as the glass substrate, an AlMoIZO glass substrate on which an indium zinc oxide transparent electrode doped with aluminum and molybdenum was formed was used instead of an ITO glass substrate.
[0075] The resulting connection structure was subjected to a pressure cooker test (PCT) in which it was kept in a thermo-hygrostat (110°C, 85% RH) for 24 hours, after which the state of the indentations made by the conductive particles on the IZO electrode was observed from the glass substrate side using a differential interference microscope and evaluated according to the following criteria: For practical purposes, a rating of B is acceptable, and a rating of A is more preferable.
[0076] (Indentation visibility evaluation criteria) Rank Evaluation criteria A: When the indentation is very clearly visible B: When the indentation is clearly visible C: When the indentation was not clearly visible
[0077] <Inspection of floating connection> As in the case of the connection reliability test, a connection structure was obtained by anisotropically conductively connecting a glass substrate and an FPC using each anisotropic conductive film prepared in the examples and comparative examples, except that a SiN glass substrate with a silicon nitride thin film formed thereon was used as the glass substrate instead of an ITO glass substrate.
[0078] The resulting connection structure was subjected to a pressure cooker test (PCT) in which the structure was kept in a thermo-hygrostat (110°C, 85% RH) for 24 hours. Then, using a differential interference microscope, the electrode part of the FPC was observed from the glass substrate side for the presence or absence of lifting, and was evaluated according to the following criteria. In practical terms, an A or B rating is sufficient, with an A rating being more preferable. The observation was performed on a total of three areas (area dimensions: 2.5 mm x 0.5 mm), one each on the left, center, and right portions of the connection structure (see FIG. 2). In addition, the ratio of the total area of the lifting at the interface between the glass substrate and the conductive particle-containing resin layer and the lifting at the interface between the insulating resin layer and the FPC to the area was calculated, and the evaluation was performed according to the following criteria. In practical terms, an A rating is sufficient, with an A rating being more preferable.
[0079] (Evaluation criteria for the floating condition of joints) Rank Evaluation criteria A: When the ratio of the floating area to the area is less than 1%. B: When the ratio of the floating area to the area is 1% or more but less than 5%. C: When the ratio of the floating area to the area is 5% or more.
[0080] [Table 3]
[0081] (Discussion of evaluation results) The anisotropic conductive films of Examples 1 to 10 were rated A or B in terms of "slitting processability," "initial adhesive strength," "connection reliability," "indentation visibility," and "state of floating of connection portion." When the anisotropic conductive films from which the cover films were peeled off after slitting in Examples 1 to 10 and Comparative Examples 1 to 7 were wound on a reel to create a wound body, no blocking occurred.
[0082] In the case of the anisotropic conductive film of Comparative Example 1, the insulating resin layer contained less than 20 mass% of a radically polymerizable acrylic compound, which reduced the cohesive strength of the insulating resin layer, and the film was rated C in the following items: "initial adhesive strength," "connection reliability" after PCT test, "indentation visibility" after PCT test, and "state of floating connection" after PCT test.
[0083] In the case of the anisotropic conductive film of Comparative Example 2, the insulating resin layer contained more than 20 mass% of an anionically polymerizable epoxy compound, which increased the brittleness of the insulating resin layer and reduced the adhesive strength, and the film was rated C in both the "initial adhesive strength" and the "state of floating of connection" after the PCT test.
[0084] In the case of the anisotropic conductive film of Comparative Example 3, a radical polymerization initiator with a one-minute half-life temperature exceeding 125°C was used in the insulating resin layer, so the “state of floating of the connection” after the PCT test was rated C.
[0085] In the case of the anisotropic conductive films of Comparative Examples 4 and 5, since no anionic polymerization curing agent was used in the insulating resin layer, the "indentation visibility" after the PCT test and the "state of floating of the connection part" after the PCT test were rated C.
[0086] In the case of the anisotropic conductive film of Comparative Example 6, a single layer of conductive particle-containing resin layer was used without using an insulating resin layer, so the ``initial adhesive strength,'' ``visibility of indentation'' after the PCT test, and ``state of floating of connection part'' after the PCT test were all rated C.
[0087] In the case of the anisotropic conductive film of Comparative Example 7, a single insulating resin layer was used without using a conductive particle-containing resin layer, so the ``initial adhesive strength,'' ``indentation visibility'' after the PCT test, and ``state of floating of connection part'' after the PCT test were all rated C. [Industrial Applicability]
[0088] The anisotropic conductive film of the present invention is multi-layered with a radically polymerizable conductive particle-containing resin layer composed of a specific component and a radically polymerizable and anionically polymerizable insulating resin layer. Therefore, the anisotropic conductive film of the present invention exhibits low-temperature rapid curing properties, realizes good initial adhesive strength for a connection structure, and even if the connection structure is mistakenly placed in a high-temperature and high-humidity environment, the connection reliability is not reduced, and good visibility of the conductive particle impressions at the connection part of the connection structure is ensured, and floating at the connection part can be prevented. Furthermore, such an anisotropic conductive film itself can be stably slit into a narrow width. Therefore, the anisotropic conductive film of the present invention is useful for manufacturing mobile electronic devices such as smartphones and tablet PCs that are evolving toward fine pitches and narrow frames. [Explanation of symbols]
[0089] 1. Insulating resin layer 2 Resin layer containing conductive particles 3. Conductive particles 4 Release base film 10 Anisotropic conductive film
Claims
1. An anisotropic conductive film having an insulating resin layer exhibiting radical polymerization and an anionic polymerization property and a conductive particle-containing resin layer exhibiting radical polymerization laminated thereon, The insulating resin layer is composed of the following components A, B, C, D and E: (Component A) a film-forming component containing a first phenoxy resin having a weight-average molecular weight of 50,000 or more and 80,000 or less, and a second phenoxy resin having a weight-average molecular weight of 30,000 or more and less than 50,000; (Component B) a radically polymerizable component containing a first acrylic compound; (Component C) an anionically polymerizable component containing an epoxy compound; (Component D) A radical polymerization initiator containing an organic peroxide having a 1-minute half-life temperature of 125° C. or less; and (Component E) an anionic polymerization curing agent containing an organic acid hydrazide compound having a melting point of 160° C. or less; Contains The conductive particle-containing resin layer comprises the following components a to d: (Component a) a third film-forming component containing a phenoxy resin; (Component b) a radically polymerizable component containing a second acrylic compound; (Component c) Conductive particles; and (component d) A radical polymerization initiator containing an organic peroxide having a 1-minute half-life temperature of 125° C. or less; An anisotropic conductive film comprising:
2. 2. The anisotropic conductive film according to claim 1, wherein the one-minute half-life temperatures of the organic peroxides of components D and b are 100°C or higher and 120°C or lower, and the melting point of the organic acid hydrazide compound of component E is 80°C or higher and 160°C or lower.
3. In the insulating resin layer, The content of component A (film-forming component) is 20.0 mass% or more and 50.0 mass% or less, and the content of the second phenoxy resin is 40 mass parts or more and 100 mass parts or less relative to 100 mass parts of the first phenoxy resin, The content of component B (radically polymerizable component) is 20.0% by mass or more and 50.0% by mass or less, The content of component C (anionically polymerizable component) is 1.0% by mass or more and less than 20.0% by mass, The content of component E (anionic polymerization curing agent) is 0.1% by mass or more and less than 10.0% by mass, and the content ratio (mass basis) of component E (anionic polymerization curing agent) to component C (anionic polymerizable component) is (= [component E] / [component C]) × 10 2 3. The anisotropic conductive film according to claim 1 or 2, wherein the content ratio (by mass) of component E (anionic polymerization curing agent) to component D (radical polymerization initiator) is 0.1 to 60.
0.
4. In the conductive particle-containing resin layer, The content of component a (film-forming component) is 15.0% by mass or more and 50.0% by mass or less, The content of component b (radically polymerizable component) is 20.0% by mass or more and 50.0% by mass or less, The content of component c (conductive particles) is 5.0% by mass or more and 45.0% by mass or less, 4. The anisotropic conductive film according to claim 3, wherein the content of component d (radical polymerization initiator) is 5 parts by mass or more and 30 parts by mass or less per 100 parts by mass of component b (radical polymerizable component).
5. the first phenoxy resin and the second phenoxy resin of component A and the third phenoxy resin of component a are all bisphenol A-type phenoxy resins; The first acrylic compound of component B and the second acrylic compound of component b are both urethane (meth)acrylates, The epoxy compound of component C is a bisphenol A type liquid epoxy resin, The organic peroxide of component D and the organic peroxide of component d are both dilauroyl peroxide, 3. The anisotropic conductive film according to claim 1, wherein the organic acid hydrazide compound of component E is salicylic acid hydrazide.
6. 3. The anisotropic conductive film according to claim 1, wherein the insulating resin layer and the conductive particle-containing resin layer further contain a polyfunctional (meth)acrylate as a crosslinking agent.
7. 7. The anisotropic conductive film according to claim 6, wherein the polyfunctional (meth)acrylate is an isocyanuric acid EO-modified di- or tri(meth)acrylate.
8. 3. The anisotropic conductive film according to claim 1, wherein the insulating resin layer and the conductive particle-containing resin layer further contain a phosphate compound or a silane coupling agent as an adhesion improver.
9. 9. The anisotropic conductive film according to claim 8, wherein the phosphoric acid ester compound is a reaction product of a 6-hexanolide addition polymer of 2-hydroxyethyl methacrylate with phosphoric anhydride.
10. 3. The anisotropic conductive film according to claim 1, wherein the insulating resin layer and the conductive particle-containing resin layer further contain a butadiene-based rubber as a softening agent.
11. 3. The anisotropic conductive film according to claim 1, wherein the conductive particle-containing resin layer contains a silica filler as a viscosity adjuster.
12. 3. A connection structure comprising a first electronic component and a second electronic component, the first electronic component and the second electronic component being anisotropically conductively connected via the anisotropic conductive film according to claim 1 or 2.
13. 3. A method for producing a connection structure, comprising: sandwiching the anisotropic conductive film according to claim 1 or 2 between a first electronic component and a second electronic component; and bonding the components together under pressure to achieve an anisotropic conductive connection.
Citation Information
Patent Citations
Epoxy resin composition, prepreg and fiber-reinforced composite material
JP2005330482A
Circuit-connecting material, connection structure of circuit terminal, and method for connecting circuit terminal
JP2007224228A
Anisotropically electroconductive adhesive film and connection structure
JP2012097226A
Anisotropic conductive film and method for manufacturing the same
JP2015149125A
Anisotropic conductive film
JP2021093357A
Cited By
Adhesive film, and connection structure and method for producing same
WO2025204071A1